Optical Fibre Technology - Farrell, Gerald (Photonics Letters of Poland, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><span style="font-size: 8.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A brief editorial overview of the papers devoted to optical fibre technology in this special edition of Photonics Letters of Poland.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>